Answers

  • qais
  • Content Quality
2016-01-19T22:40:25+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
n term sum = 3n²/2 + 13n/2
as we know that nth term = (Sum of nth term ) -( sum of (n-1)th term)
method 1
so 25th term = (sum of 25 terms) - ( sum of 24 terms)
                     =(3×(25)²/2 +(13×25)/2) - ( 3×(24)²/2 + (13×24)/2)
                     = 1100 - 1020
                     = 80
method 2
1st term = 8
sum of 2 terms = 19
2nd term = 19 - 8= 11
so. difference = 11- 8 = 3
25th term = (8 + (25 -1)×3) = 80
0